Pengaruh Perbedaan Konsentrasi Hormon Benzyl Amino Purine (BAP) Terhadap Penampilan Karakter Agronomi Beberapa Varietas Bawang Merah (Allium ascalonicum L.) di Dataran Rendah - Rahmah, Kamilah; Azizah, Elia; Rianti, Winda (UNIVERSITAS LABUHANBATU, 2023)
Shallot is one of the horticultural commodities that has high economic value because its existence is very much needed by the people of Indonesia. This study aims to determine the exact concentration of BAP that can provide the best agronomic performance on several varieties of shallots in the lowlands. This research was conducted from December 2022 to May 2023 at the Screen House of the Faculty of Agriculture, Singaperbangsa University, Karawang which is located in Pasir Jengkol Village, Majalaya District, Karawang Regency. The research method used was Factorial (RAK) which consisted of 12 treatments and each treatment was repeated 3 times so that there were 36 experimental units in total. The first factor is variety which consists of 3 levels, namely v1 (Dayak), v2 (Sumenep), v3 (Bima Brebes). The second factor was the concentration of BAP which consisted of 4 levels, namely b1 (0 ppm), b2 (25 ppm), b3 (50 ppm), b3 (75 ppm). The effect of treatment was analyzed using analysis of variance and if the F test at 5% level was significant, then it was continued with a 5% DMRT follow-up test. The experimental results showed that there was no interaction between the several varieties and BAP concentrations on all observed parameters. however, the results showed a significant effect on the independent factor of the variety. Variety v1 (Dayak) was able to produce the highest number of tillers, fresh weight of stover, fresh weight of tubers per clump, dry weight of stover and dry weight of tubers per clump compared to v2 (Sumenep) and v3 (Bima Brebes). The independent factor of BAP concentration did not have a significant effect on all observed parameters.